Witches, Victims, and Villains: #MeToo and the Political Polarization of Sexual Violence - Shoaf, Hannah (Violence against women, 2024)
#MeToo sought to combat sexual violence but evolved into a polarizing movement in the United States. Using a random sample of 5,153 tweets with #MeToo posted between 2017 and 2019 to explore the language and themes individuals use to polarize conversations around sexual violence, we find that MeToo supporters used rights-and-justice-focused language to advocate for survivors. In contrast, MeToo detractors employed legal and violent language to victimize the alleged perpetrators and villainize victims of sexual violence and their supporters. This demonstrates how “linguistic hijacking” unfolded online, with movement opponents co-opting key terms (like “victim”) to undermine movement supporters’ goals.